Avaliação da atividade antimicrobiana de extrato do fruto, folha e casca de caule do Zizyphus joazeiro Mart - Melo, Maria Do Socorro Fernandes (2010)
The study of medicinal plants enables the discovery of new bioactive compounds. The emergence of microorganisms resistant to antibiotics reinforces this research. Among the microorganisms resistant Mycobacterium tuberculosis shows continuous change by changing their susceptibility profile, resulting in treatment failure. The search for antimicrobial properties of plant extracts and their constituents have been encouraged and intensified. Thus, among many plant species to be investigated, we highlight the juazeiro. Belonging to the family Rhamnaceae, which presents in its composition a wide variety of bioactive secondary metabolites, especially terpenoids, alkaloids of great medical interest. Its main feature is that this tree resists drought very well in the northeastern and became so useful to men, providing shade and fruit, and animals that eat their leaves mucilage. The aim of this study was to evaluate the antimicrobial activity in vitro of extracts juazeiro front of microorganisms, including yeasts, Gram-positive bacteria, Gram-negative bacterium Mycobacterium bovis using the technique of agar diffusion. All extracts showed antimicrobial activity. Among the microorganisms evaluated only Bacillus subtilis, Staphylococcus aureus and Candida albicans were sensitive. None of the evaluated extracts had antimycobacterial activity against Mycobacterium bovis